PENINGKATAN KUALITAS NUTRISI TEPUNG DAUN LAMTORO SEBAGAI PAKAN IKAN DENGAN PENAMBAHAN EKSTRAK ENZIM CAIRAN RUMEN DOMBA - Fitriliyani, Indira; Harris, Enang; Mokoginta, Ing; Nahrowi, Nahrowi (BERITA BIOLOGI, 2010)
The aim of this experiment is to evaluate the nutrient quality of leucaena leaf meal (LLM) with addition of sheep rumen fluid enzyme for nile tilapia feed and incubated in vitro either for 2 or 24 hours. This experiment was arranged in a completely randomized design with 6 treatments and 3 replications. Those treatments were enzyme levels of 0, 20, 40, 60, 80, and 100 ml/ kg LLM. Results showed that nutrient quality of LLM with addition of sheep rumen fluid enzyme that incubated for 24 hours had the best result compared to that incubated for 2 hours. This finding significantly affected (PO.05) on the increase of sugar release (76.97%), soluble glucose (21.27%) and soluble protein (37.7%). It is concluded that sheep rumen fluid enzyme has a great potential for improving nutritional quality of leucaena leaf meal of fish feed.